The influence of country personality dimensions on intentions to recommend visiting: the preponderance of assiduousness and wickedness - Búrcio, C.; Vinhas da Silva, R.; Salgueiro, M. F. (Transnational Marketing Journal, 2015)
The purpose of the current research is to investigate the relationships between country personality dimensions and consumer behavioural intentions, and to examine in detail the perceived personality of a stimulus-country. A convenience sample of 130 individuals from Brazil was surveyed and 115 usable questionnaires were analyzed. Portugal was chosen as the country for scrutiny and the questionnaire was delivered in Portuguese. Country personality was measured using the 24 items of personality traits six dimensions scale of d’Astous & Boujbel (2007). The research findings suggest that consumers ascribe personality characteristics to countries. All the items show high factorial weights, and in the proposed model the percentage of the variance of the intention to recommend explained by the perceived country personality dimensions equals around 23%. Assiduousness showed a positive significant influence on intention to recommend, whereas wickedness showed a significant negative influence. The findings suggest differences from the comparable earlier studies. Practical and theoretical implications are discussed. Complementarily, and as suggested by the personality traits frequency analysis, Portugal is seen as a traditionalist country